A Study on Export Effectiveness: A Case Study of Nepal - Khatri, Mukti Bahadur (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
Historically, in many countries around the world exports have a significant role in contributing to employment generation and sustain economic growth. So, this research analyses the effectiveness of export in Nepal by using a regression analysis for the periods of 1975-2021 of 47 annual time series. According to empirical findings, Nepalese RGDP has an inverse impact on export while RGDP of India, exchange rate of US Dollar and trade liberalization are insignificant. So, there is a need for structural transformation to improve productivity, reduce cost of factor inputs and create the right business as well as business friendly policy, favorable exchange rate, legal and political atmosphere to attract efficient business activity along with good governance which ultimately increases GDP growth; employment, export and capital inflows respectively in national economy and that improve quality of life.